Food advertising during children's television programmes in Italy. Issue 14 (18th October 2021) - Gallus, Silvano; Borroni, Elisa; Stival, Chiara; Kaur, Sharanpreet; Davoli, Sofia; Lugo, Alessandra; Effertz, Tobias; Garattini, Silvio; Scaglioni, Silvia
Abstract: Objective: Previous studies from European countries noted that food products promoted on TV for children did not comply with international guidelines, including the World Health Organization European Nutrient Profile Model (WHO-ENPM) and the EU Pledge Nutrition Criteria (EU-PNC, an initiative developed by leading food companies). We aim to provide new data from Italy. Design: Evaluation of Italian TV advertisements. Data on nutritional values for food product advertised were compared with nutritional standards issued by the WHO-ENPM and the EU-PNC. Setting: In total, 180 h of TV programmes from six Italian channels, 2016–2017. Participants: Eight hundred and ten consecutive advertisements during children's programmes. Results: Out of 810 advertisements, 90 (11·1 %) referred to food products. Among these, 84·5 % of the foods promoted did not meet the WHO-ENPM and 55·6 % the EU-PNC guidelines. Advertisements promoting sweet and salty snacks (i.e. ≥ 70 % of all foods) v . other food products showed higher non-compliance with both the WHO-ENPM (OR: 73·8; 95 % CI: 4·09, 1330) and the EU-PNC (OR: 9·21; 95 % CI: 2·82, 30·1). Conclusions: In Italy, most food advertisements during children's programmes are not compliant with European nutritional standards. Almost all the advertisements for snacks do not meet international guidelines. As the WHO-ENPM guidelines do not propose standards for all the food products, including meals, there is an urgent need to define independent and easy-to-read guidelines for food advertisements targeting children. As a first step towards the complete ban of food advertisements targeting children recommended by other researchers, these guidelines should be enforced by all the TV broadcasts.